Controlled Regioselective Amination of Peryleneimides. Issue 3 (12th December 2014) - George, Lijo; Ahmed, Zafar; Lemmetyinen, Helge; Efimov, Alexander
Abstract: Perylenediimides (PDIs) and perylenemonoimide diesters (PMIs) can be selectively substituted at the 1, 6‐ or 7, 12‐ positions of the bay region, respectively, by direct amination reactions. The reactions proceed by the formation of a perylene radical anion and its subsequent oxidation, and the yields range from 20–97 %. The amination can be tuned to obtain either mono‐ or disubstituted perylenes by varying the oxidants involved. The presence of the imide cycle is crucial for the transformation, although the amination occurs regioselectively at the bay‐region positions distant from the imide cycle. Abstract : An efficient and direct protocol for the highly regioselective amination of peryleneimides has been developed. The method involves the stepwise formation of a radical anion, which is then oxidized in situ under mild reaction conditions.